Prodrugs available on the Brazilian pharmaceutical market and their corresponding bioactivation pathways - Roberto Parise Filho; Michelle Carneiro Polli; Silvio Barberato Filho; Monique Garcia; Elizabeth Igne Ferreira (Universidade de São Paulo, 2010)
The aim of this paper was to emphasize the importance of prodrug design to therapy, by examining examples available on the Brazilian pharmaceutical market. The principles of prodrug design are briefly discussed herein. Examples of prodrugs from many important therapeutic classes are shown and their advantages relative to the drugs they are derived from are also discussed. Considering the importance of these therapeutic classes, from both therapy and economic standpoints, prodrug design is a very valuable aspect in the research of new drugs and for the pharmaceutical industry as a whole. O objetivo do trabalho foi ressaltar a importância do planejamento de pró-fármacos para a terapia, por meio de exemplos disponíveis no mercado farmacêutico brasileiro. Os princípios da latenciação são sucintamente discutidos. Apresentam-se exemplos de pró-fármacos de muitas classes terapêuticas importantes e as vantagens relativas aos fármacos dos quais derivam são, também, discutidas. Considerando-se a importância dessas classes terapêuticas, tanto do aspecto terapêutico quanto do econômico, o planejamento de pró-fármacos representa aspecto de grande valor na busca de novos fármacos e na indústria farmacêutica como um todo.